Wer ist von Altersarmut bedroht? - Maria Lewicki; Berthold U. Wigger (Wirtschaftsdienst, 2013)
Altersarmut ist gegenwärtig in Deutschland ein zentrales Thema. Für die Zukunft wird ein deutlicher Anstieg befürchtet. Wer aber ist davon bedroht? Die Autoren werfen einen detaillierten Blick auf typisierte Erwerbsverläufe und deren Folgen für die Höhe der Renten. Sie kommen zu dem Ergebnis, dass eine ursachengerechte Bekämpfung der Altersarmut schon bei der Armut vor Eintritt in das Rentenalter ansetzen sollte. – – Which groups have particularly low pension entitlements and are therefore most at risk of poverty in old age? Participation in the labour force for some individuals may be interrupted for a variety of reasons, including education, unemployment, raising children or caring for relatives, all of which result in low pensions. Those who are most at risk of poverty in old age are individuals with low earnings, frequent or long periods of unemployment, and single, unemployed mothers. In other words, those impoverished while young are most likely to remain impoverished into old age. Poverty among the elderly should therefore be addressed with the same instruments with which poverty is being fought in earlier stages of life, rather than through changes in the statutory pension insurance system.
Keywords: H55; I32; I38; 330; Armut; Alte Menschen; Erwerbsverlauf; Deutschland